(untitled) (Swiss Medical Weekly, 2015)
Mechanical ventilation with high tidal volumes (VT) has been common practice in operating theatres because this strategy recruits collapsed lung tissue and improves ventilation-perfusion mismatch, thus decreasing the need for high inspired oxygen concentrations. Positive end-expiratory pressure (PEEP) was not used routinely because it was thought to impair cardiovascular function. Over the past two decades there have been advances in our understanding of the causes and importance of ventilation-induced lung injury based on studies in animals with healthy lungs, and trials in critically ill patients with and without acute respiratory distress syndrome. Recent data from randomised controlled trials in patients receiving ventilation during general anaesthesia for surgery have demonstrated that lung-protective strategies (use of low VT, use of PEEP if indicated, and avoidance of excessive oxygen concentrations) are also of importance during intraoperative ventilation.